A Neonatal Murine Escherichia coli Sepsis Model Demonstrates That Adjunctive Pentoxifylline Enhances the Ratio of Anti- vs. Pro-inflammatory Cytokines in Blood and Organ Tissues - Speer, Esther M.; Diago-Navarro, Elizabet; Ozog, Lukasz S.; Raheel, Mahnoor; Levy, Ofer; Fries, Bettina C. (Frontiers in Immunology, 2020)
Introduction: Neonatal sepsis triggers an inflammatory response that contributes to mortality and multiple organ injury. Pentoxifylline (PTX), a phosphodiesterase inhibitor which suppresses pro-inflammatory cytokines, is a candidate adjunctive therapy for newborn sepsis. We hypothesized that administration of PTX in addition to antibiotics decreases live bacteria-induced pro-inflammatory and/or enhances anti-inflammatory cytokine production in septic neonatal mice without augmenting bacterial growth. Methods: Newborn C57BL/6J mice (<24 hours (h) old) were injected intravenously with 105 colony forming units (CFUs)/g weight of a bioluminescent derivative of the encapsulated clinical isolate Escherichia coli O18:K1. Adequacy of intravenous injections was validated using in vivo bioluminescence imaging and Evans blue. Pups were treated with gentamicin (GENT), PTX, (GENT+PTX) or saline at 0h, 1.5h or 4h after sepsis initiation, and euthanized after an additional 4h. CFUs and cytokines were measured from blood and homogenized organ tissues. Results: GENT alone inhibited bacterial growth, IL-1b and IL-6 production in blood and organs. Addition of PTX to GENT profoundly inhibited E. coli-induced TNF and enhanced IL-10 in blood of newborn mice at all timepoints, whereas it primarily upregulated IL-10 production in peripheral organs (lung, spleen, brain). PTX, whether alone or adjunctive to GENT, did not increase microbial colony counts in blood and organs. Conclusion: Addition of PTX to antibiotics in murine neonatal E. coli sepsis promoted an anti-inflammatory milieu through inhibition of plasma TNF and enhancement of IL-10 production in plasma and organs without increasing bacterial growth, supporting its utility as a potential adjunctive agent for newborn sepsis.